Characterization of Alluvial Soil for Growth of Chinese Betel (Peperomia pellucida L.) - Silahooy, Charles (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
This study aims to determine the characterization of alluvial soil as a place to grow Chinese betel (peperomia pellucida L.) in Ambon city. Parameters studied included morphological characterization of alluvial soil and description of Chinese betel nut (Peperomia pellucid a L.). The results of observations in the field and analysis of soil samples in the laboratory that have been collected are used as material to identify soil morphological characterization. Meanwhile Chinese betel nut (Peperomia pellucid a L.) collected from alluvial soil was selectively explored by exploring the research area using the Cruise Method. Furthermore, a phytochemical test was carried out to determine its phytochemical content. The results showed that the color of the soil and the rusty color of the alluvial soil in Ambon City was generally brown. The alluvial soil structure at the study site has an O horizon with a soil layer thickness of 17 cm, an A horizon with a thickness of 45 cm soil lumpy structure and a Bw horizon with a soil thickness of 30 cm and the C horizon with a thickness of 65 cm is classified as having a globular lumpy soil structure, It has a high clay and silt content. The lower the soil solum, the lower the C-organic content. The soil in Ambon city has moderate fertility. Low base saturation is associated with low C-organic content in the soil. Chinese sirih that grows on alluvial soil types in Ambon City contains several classes of compounds that are beneficial to health like flavonoids, alkaloids, tripenoids, phenolics, tannins and saponins so that they have ethnomedicin effects such as anticancer, antimicrobial, antidiabetic, antihypertensive and antioxidant activities.